The investigation of the cranberry (Vaccinium oxycoccos L.) concentrated juice antimicrobial activity - K. M. Yatsiuk; M. I. Feodorovska; R. V. Kutsyk (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The urinary system infections is one of the most common diseases of the genitourinary system in women. Of particular interest in the prevention and treatment of chronic cystitis is the consumption of the cranberry (Vaccinium oxycoccos L.) fruits. This plant has long been used in urological practice due to the content of proantocianidins, flavonoids, organic acids (benzoic, citric, quinic, ursolic), pectin substances, vitamins, microelements etc. Numerous clinical studies (including randomized, double-blind, placebo-controlled) reveal statistically reliable efficiency of cranberry juice in the forms of concentrates, cocktails and capsules to urinary system infections prevention in women. Since the main pathogens of urinary system infections are Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus, the aim of our work was to study the antimicrobial properties of the cranberry concentrated juice. Comparative testing of antimicrobial activity was performed using micromethod of diffusion in agar. The carried out study indicates that the concentrated juice maintains antimicrobial properties to the most common uropathogenic microorganisms. Effective antimicrobial concentration was found according with analysis of microbial cultures growth curves in a nutrient medium with various juice dilutions. Gram-positive bacteria (S. aureus, E. faecalis) are more sensitive to the cranberry concentrated juice than gram-negative (E. coli and P. aeruginosa). The adhere ability to a solid surface with the subsequent formation of biofilm is an important factor in the uropathogenic bacteria virulence. Therefore, the next step was to study the effect of cranberry juice biologically active compounds on the biofilms formation in the uropathogenic bacteria broth cultures. It was determined that cranberry juice suppresses the biofilm formation of S. aureus with the greatest intensity. It was observed the 45,3-55,8% reduction of the biofilm creating intensity in the presence of the condensed juice subbacteriostatic dilutions. When the condensed juice was diluted as 1:160, inhibition of E. faecalis biofilm formation ability on 44,90% was detected. The effect of cranberry biologically active compounds on the biofilms formation by gram-negative bacteria was observed in the range of 20%. Thus, the obtained cranberry concentrated juice can be recommended as the remedy for application in prevention of recurrent urinary system infections.